Thermal Effusivity And Refractive Index Of Oil-Alcohol Mixtures - Mohamad Al-Asfoor, Firas Kamel (2009)

(untitled)
The open photoacoustic cell technique has been used for thermal effusivity measurements on pure liquids and liquid mixtures. The thermal effusivity was determined from the captured photoacoustic signal amplitude as a function of modulated frequency. The chosen samples for liquids were ethanol, methanol, glycerol, virgin olive oil, virgin coconut oil and distilled water. The thermal effusivity values which were obtained for these liquids were in the range from 0.0524 W s1/2 K-1 cm-2 to 0.1522 W s1/2 K-1 cm-2 with acceptable error about (± 0.041). For oil- alcohol mixtures, two kinds of alcohol (ethanol and methanol) were mixed separately with two types of virgin oils and eleventh different percentages for each oil- alcohol mixture sets were obtained. Thermal effusivity values and the density of virgin olive oil-ethanol mixtures decreased with the increasing of ethanol composition in the mixture. The thermal effusivity values for virgin oil- ethanol mixture varied from 0.0524 W s1/2 K-1 cm-2 to 0.0589 W s1/2 K-1 cm-2, and the density By using the minimum deviation method, the refractive index was determined for the samples. Distilled water was used to calibrate the experimental setup. The experiment was carried out at room temperature and a laser source with 632.8 nm wavelength was used. The refractive index of distilled water was 1.332 which is in good agreement with literature. Using the same laser source, the refractive indices of the mixture samples were measured. Virgin olive oil-ethanol mixtures has refractive index varied from 1.3597 to 1.4652. The refractive indices of virgin olive oil-methanol mixture varied from 1.3266 to 1.4564. The same method was used to measure the refractive index of virgin coconut oil-ethanol mixtures and it was found that these values varied from 1.3597 to 1.4524. The refractive index measurements were carried for virgin coconut oil-methanol mixtures and it was found that the refractive index values were varied from 1.3266 to 1.4524. In this study it was found that the refractive index for all the mixture samples decreased gradually while the alcohol percentage increased in the mixture. The FTIR measurements ranging from 600 cm-1 to 4000 cm-1 were carried out to determine functional groups of the mixtures using Fourier Transform Infrared. Generally the FTIR spectra for all mixtures shows that the five important peaks explaining the stretching absorption due to aldehyde (C= O) and esters (C-O), bending absorption (methylene (CH2) and methyl (CH3) groups) and double bond absorptions (C= O) are strong in pure oils and oil- alcohol mixtures.